anonymous
  • anonymous
Please help medals/fan will be given!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
1. If f(x) = 3x + 1 and g(x) = 2x − 4, find f[g(2)]. 25 4 zero 1 2. If f(x) = −x − 1 and g(x) = 4x − 1, find f[g(−2)] −10 −9 −13 8 3. If f(x) = x + 3 and g(x) = −4x − 1, find g[f(4)]. 21 −21 19 −19 4. If f(x) = 4x + 1 and g(x) = −x − 2, find (f + g)(−1). −4<==== 4 −6 −8 5. If f(x) = 2x − 2 and g(x) = 3x − 1, find (f − g)(4). 17 −17 5 −5 6. If f(x) = x − 2 and g(x) = −2x − 1, find (f • g)(9) 19 −18 zero −19 7. If f(x) = −2x − 4 and g(x) = x + 4, find ()(−8). −3 3 −1 1 8. If f(x) = x − 4 and g(x) = x − 2, find f[g(−6)]. 9 3 −9 −3 9. If h(x) = 3x − 1 and j(x) = −2x, find h[j(2)]. 11 −11 13 −13<==== 10. If r(x) = 3x − 1 and t(x) = −4x − 1, find (r + t)(7). 9 −9<==== −49 49
hba
  • hba
Please post a single question at a time.
anonymous
  • anonymous
ok can you give an answer to at least one please

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
@hba
hba
  • hba
Giving direct Answers is not allowed on OS.
anonymous
  • anonymous
1 for the first question
anonymous
  • anonymous
to get that you plug in 0 into g(x) then plug your solution 0 into f(x)
anonymous
  • anonymous
and you get 1
anonymous
  • anonymous
I didn't say don't explain
anonymous
  • anonymous
Thank you @marvin.cling
anonymous
  • anonymous
i explained do you want more explanation? \[g(2)=2(2)-4=0, f(g(2))= 3(0)+1=1. How's that for an explanation\]
anonymous
  • anonymous
sorry i meant two not 0
anonymous
  • anonymous
no just plaese answer my next post

Looking for something else?

Not the answer you are looking for? Search for more explanations.